A 2.45 GHz microstrip antenna with harmonics suppression capability by using defected ground structure - Shaharil Mohd Shah; M. Mohamad; S. A. Hamzah; Z. Z. Abidin; F. C. Seman; N. Katiran; H. A. Majid; A. Ashyap; S. Mohamad (Bulletin of Electrical Engineering and Informatics, 2020)
In this work, a microstrip patch antenna with an inset feed and defected ground structure (DGS) is designed at the resonant frequency of 2.45 GHz. The antenna is designed on a FR-4 substrate with a dielectric constant, εr of 4.5, loss tangent, tan δ of 0.019 and thickness, h of 1.6 mm. The technique of DGS is used to avoid the use of additional circuits in the antenna to suppress the harmonics. By introducing a single and additional slots DGS at both ends on the antenna ground plane, the proposed microstrip patch antenna is able to suppress the higher order harmonics. The reflection coefficient, S11 is -38.75 dB at 2.45 GHz. The proposed antenna have suppressed the higher order harmonics effectively from -38.04 dB to -2.61 dB at 4.54 GHz and from -13.08 dB to -1.38 dB at 5.76 GHz. The prototype of the antenna is fabricated for the verification of the design. The simulated and measured results are found to be in a good agreement.